Establishing Values of Insights Academic Communication for Students - Khotibul Umam , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
The development of communication technology in the era of globalization has caused the realm of interpersonal communication not only to be done in the form of face-toface but also through various modern media or what is commonly called mediated interpersonal communication. The sophistication of information and communication technology is now able to accommodate this. The existence of telephones, SMS (short message services), video calls, to the features offered by several social media are very supportive of communication done over long distances. Forms of communication also vary, from formal to informal. In terms of politeness in language, mediated communication can trigger users to ignore social and cultural values and prioritize the effectiveness of messages. Communication politeness is closely related to the use of good, polite, and correct language in accordance with norms and manners. The shift of times, cultural values, and the mindset of an increasingly advanced and modern society contributes to the politeness of communication. Modern and advanced mindset like this tends to forget the values / norms that already exist and are easily facilitated in everything. Not infrequently things that were once considered taboo can now become a norm, which used to be considered impolite now may be considered normal, which used to be impossible to do now it is very possible to be done. The politeness of language is reflected in the procedure for communicating through verbal signs or language procedures. When communicating, language users must submit to cultural norms, not just convey the ideas we think about. The language procedure must be in accordance with the cultural elements that exist in the community where life and use of a language in communication.